Reliability testing of the HEARTSMAP psychosocial assessment tool for multidisciplinary use and in diverse emergency settings. Issue 8 (6th March 2018) - Virk, Punit; Stenstrom, Rob; Doan, Quynh
Abstract: Objective: HEARTSMAP is a tool developed to facilitate assessment and management of paediatric mental health (MH) patients by emergency department (ED) clinicians. We evaluate the inter-rater reliability of HEARTSMAP when administered by clinicians of various backgrounds. Methods: In a cross-sectional study initiated in 2016, collaborating clinician evaluators (n=16) applied the HEARTSMAP tool to evaluate a set of 50 fictional clinical vignettes, digitally in an approach consistent with the anticipated tool's access and usage in clinical settings. Evaluators came from different types of health centres from across the province of British Columbia (Canada), including remote/rural, regional and urban academic health centres. Results: We report moderate to near excellent agreement, overall among clinicians for all 10 of the tool's psychosocial sections (κ=0.43 to 0.93) and domain scores (κ=0.75 to 0.90), with acceptable agreement across all tool-triggered service recommendations (κ=0.36 to 0.65). Conclusions: Our findings show that HEARTSMAP may be reliably used by ED clinicians in assessing MH issues among youth. Results from this study will assist in informing the wider clinical implementation of HEARTSMAP as a standard assessment tool, in diverse emergency care settings.